2022
DOI: 10.1097/iae.0000000000003437
|View full text |Cite
|
Sign up to set email alerts
|

Bacillary Layer Detachment in a Korean Cohort With Neovascular Age-Related Macular Degeneration

Abstract: To evaluate the incidence and characteristics of bacillary layer detachment (BALAD) in neovascular age-related macular degeneration.Methods: This retrospective study was performed at Kim's Eye Hospital in South Korea. Patients who were diagnosed with neovascular age-related macular degeneration between January 2017 and December 2017 were included. The incidence of BALAD was compared among different types of macular neovascularization (MNV). The best-corrected visual acuity and central retinal thickness at diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…We also observed a hyper-reflective band contiguous to an attenuated EZ on the floor of the BALAD. These findings have been reported in the literature [ 10 , 14 , 15 , 16 , 20 , 21 ]. Ramtohul et al postulated that floor hyper-reflectivity could be related to the remaining mitochondria of the residual photoreceptor IS on the RPE–basal lamina–Bruch membrane complex.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We also observed a hyper-reflective band contiguous to an attenuated EZ on the floor of the BALAD. These findings have been reported in the literature [ 10 , 14 , 15 , 16 , 20 , 21 ]. Ramtohul et al postulated that floor hyper-reflectivity could be related to the remaining mitochondria of the residual photoreceptor IS on the RPE–basal lamina–Bruch membrane complex.…”
Section: Discussionsupporting
confidence: 89%
“…It was predominantly associated with type 1 and 2 mixed MNV, higher fluid volumes, increased EZ attenuation, and sub-RPE disease [ 15 ]. Instead, Jae Hui Kim et al reported an incidence of bacillary detachment in 4.5% (20 of 442) of the patients examined [ 16 ]. In a Korean cohort, Kim et al observed that the incidence of BALAD was significantly different in the types of MNV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Special attention has recently been given to studying BALAD as a prognostic indicator in exudative macular pathologies, especially neovascular age-related macular degeneration [ 2 – 5 ], and in inflammatory choroidal conditions such as Vogt-Koyanagi-Harada disease [ 6 ]. This may have led to an overrepresentation of these cases within the literature [ 1 ].…”
Section: Introductionmentioning
confidence: 99%